Multi-stage Reactive Formation of Troctolites in Slow-spreading Oceanic Lithosphere (Erro–Tobbio, Italy): a Combined Field and Petrochemical Study. (29th March 2019) - Basch, Valentin; Rampone, Elisabetta; Crispini, Laura; Ferrando, Carlotta; Ildefonse, Benoit; Godard, Marguerite
Abstract: Many recent studies have investigated the replacive formation of troctolites from mantle protoliths and the compositional evolution of the percolating melt during melt–rock interaction processes. However, strong structural and geochemical constraints for a replacive origin have not yet been established. The Erro–Tobbio impregnated mantle peridotites are primarily associated with a hectometre-size troctolitic body and crosscutting gabbroic dykes, providing a good field control on melt–rock interaction processes and subsequent magmatic intrusions. The troctolitic body exhibits high inner complexity, with a host troctolite (Troctolite A) crosscut by a second generation of troctolitic metre-size pseudo-tabular bodies (Troctolite B). The host Troctolite A is characterized by two different textural types of olivine, corroded deformed millimetre- to centimetre-size olivine and fine-grained rounded undeformed olivine, both embedded in interstitial to poikilitic plagioclase and clinopyroxene. Troctolite A shows melt–rock reaction microstructures indicative of replacive formation after percolation and impregnation of mantle dunites by a reactive melt. The evolution of the texture and crystallographic preferred orientation (CPO) of olivine are correlated and depend on the melt/rock ratio involved in the impregnation process. A low melt/rock ratio allows the preservation of the protolith structure, whereas a high melt/rock ratio leads to the disaggregation of the pre-existing matrix. The mineral compositions in Troctolite A define reactive trends, indicative of the buffering of the melt composition by assimilation of olivine during impregnation. The magmatic Troctolite B bodies are intruded within the pre-existing Troctolite A and are characterized by extreme textural variations of olivine, from decimetre-size dendritic to fine-grained euhedral crystals embedded in poikilitic plagioclase. This textural variability is the result of olivine assimilation during melt–rock reaction and the correlated increase in the degree of undercooling of the percolating melt. In the late gabbroic intrusions, mineral compositions are consistent with the fractional crystallization of melts modified after the reactive crystallization of Troctolites A and B. The Erro–Tobbio troctolitic body has a multi-stage origin, marked by the transition from reactive to fractional crystallization and diffuse to focused melt percolation and intrusion, related to progressive exhumation. During the formation of the troctolitic body, the melt composition was modified and controlled by assimilation and concomitant crystallization reactions occurring at low melt supply. Similar processes have been described in ultraslow-spreading oceanic settings characterized by scarce magmatic activity.